Organizational Support and Servant Leadership: the Mediating Role of Work Motivation and Integrity on Work Productivity - Muhammad Andriansyah; Bibin Rubini; Sri Setyaningsih (Journal of Vasyl Stefanyk Precarpathian National University)
This research aims to identify the optimal strategy to enhance the work productivity of lecturers at Muhammadiyah University Jakarta by reinforcing organizational support, servant leadership, work motivation, and integrity. Employing a quantitative approach, this study distributed a survey to 164 lecturers. The data were analyzed using path analysis to evaluate the direct and indirect relationships among variables and the SITOREM method to pinpoint indicators requiring improvement or development. The findings demonstrate that organizational support and servant leadership significantly and directly impact work productivity. Additionally, their effects are partially mediated by work motivation and integrity. However, the direct influence of organizational support and servant leadership outweighs the indirect effects mediated by motivation and integrity. This suggests that while motivation and integrity are important, strengthening organizational support and servant leadership yields a more substantial impact on productivity. To optimize productivity, weaker areas such as economic added value and fairness in rewards need improvement. Specific attention should also be given to indicators such as cost efficiency and accountability. Organizational support can be enhanced by promoting fairness in reward distribution, increasing involvement in decision-making, ensuring resource availability, and fostering supportive supervision. The implications of this study provide practical guidance for colleges and universities aiming to improve lecturers’ productivity. This research serves as a valuable reference for academic institutions striving to create a supportive environment that fosters continuous productivity improvement among their staff, ultimately contributing to institutional success and societal impact.